Effect of Dietary Carotenoids on Reproducers of Amazon River Prawn Macrobrachium amazonicum. Part 1: Metabolism, Morphometric / Zootechnical Indexes, Body Composition and Gametes - Costa, Daniel Pereira da; Castilho, Claudiana de Lima; Santos, Uclédia Roberta Alberto dos; Gemaque, Tainára Cunha; Damasceno, Leandro Fernandes; Lima, Jô de Farias; Filho, Kleber Campos Miranda (Journal of Agricultural Studies, 2021)
The inclusion of natural extracts and solution of synthetic astaxanthin in the Macrobrachium amazonicum diet were tested to verify their effect on performance, body indexes and total accumulation of astaxanthin in the reproductive tissues and gametes of this crustacean in comparison with newly captured wild animals. The experiment was randomized in blocks (five treatments with three replicates). Four groups were submitted, during 20 days, to diets in recirculation tanks: control diet (CONT); diet containing natural extract of “buriti” (CAR); diet with inclusion of natural “urucum” extract (BIXN), diet with synthetic astaxanthin (ASTX) and NATURAL group (not fed with ration). 180 prawns were used, with 60 males (6.08±1.96 g) and 120 females (4.55±1.03 g) distributed in five groups containing four males and eight females each. There were no significant differences in performance and body indexes. The number of released spermatozoids, live spermatozoids, body and egg pigmentation was higher in BIXN and ASTX treatments. The ASTX treatment was superior to the NATURAL group in the body pigmentation of females and eggs and release of spermatophores by males. These results demonstrate that the use of natural and artificial carotenoid pigments in the diet are beneficial for reproduction of M. amazonicum.